1993
DOI: 10.1111/j.1532-5415.1993.tb06172.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adaptations and Compliance to Exercise Training between Middle‐Aged and Older Men

Abstract: The results of this study involving small groups of carefully screened middle-aged and older men suggest that the time course and magnitude of physiologic adaptations to aerobic training are similar between age groups when the training regimen is the same. Neither age group showed alterations in psychologic parameters nor experienced orthopedic injuries with training. The older group showed greater interest in continued participation in a supervised exercise program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…However, exercise training is capable of increasing endurance capacity to the required level in most of the elderly intending to engage in mountaineering activities. Most specific studies indicate that sedentary persons can improve their V · O 2 max by about 15% or more after three months of endurance training [116,117]. Exercise training impacts on several areas, including aerobic capacity, haemodynamic and autonomic nervous system function, and peripheral vascular and muscular function [115].…”
Section: Training Of Endurance Performance In the Elderly Mountaineermentioning
confidence: 99%
“…However, exercise training is capable of increasing endurance capacity to the required level in most of the elderly intending to engage in mountaineering activities. Most specific studies indicate that sedentary persons can improve their V · O 2 max by about 15% or more after three months of endurance training [116,117]. Exercise training impacts on several areas, including aerobic capacity, haemodynamic and autonomic nervous system function, and peripheral vascular and muscular function [115].…”
Section: Training Of Endurance Performance In the Elderly Mountaineermentioning
confidence: 99%
“…Há indicativos de que o treino leve a adaptações mais lentas na população idosa. Entretanto, não é claro se isso se deva a uma taxa mais lenta de adaptação ao treino ou a um aumento mais gradual na intensidade dos exercícios, que é observado quando o programa é dirigido à população idosa (Sheldahl et al, 1993).…”
Section: Envelhecimentounclassified
“…Independente do programa de exercício físico, a manutenção da prática é fundamental para a permanência dos seus benefícios, o que deve ser considerado durante a organização e administração dos exercícios (Sheldahl et al, 1993;Williams e Lord, 1995;Caromano, 1998;Devons, 2002). …”
Section: Envelhecimentounclassified
“…1986). Besides improving cardiovascular functioning in older adults (Blumenthal et al, 1991;Morey et al, 1989;Sheldahl et al, 1993), Isaacs et al (1992 demonstrated that exercise produces increased vascularization in the brains of rats. Two additional studies (Gentile et al, 1987;Pysh and Weiss, 1979) have reported increased brain cell hypertrophy and complexity as a result of exercise.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%